THE EFFECT OF SERLI PRACTICUM MODULE ON MAGNETIC MATERIAL TOWARDS STUDENTS LEARNING OUTCOMES IN OFFLINE LEARNING - Melyani Sari Sitepu; Azizah Azizah; AnnisaNur Diani (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effect of offline learning assisted by the Serli practicum module on magnetic material on the learning outcomes of sixth grade students of SD Negeri 1 Binangga. The type of this research is quantitative research with experimental research type using Quasi Experiment method with Nonequivalent Control Group Design. The subjects in this study were students of class VI SD Negeri 1 Binangga, totaling 23 people. There were 12 experimental class students and 11 control class students. Data retrieval was carried out using multiple choice questions, and data analysis used prerequisite tests, namely normality and homogeneity tests and hypothesis testing using independent sample t-test tests which were analyzed using SPSS Statistics Version 25. Based on the results of this study, it showed a significant value of 0.000 0,05 then accept the Ha hypothesis and reject Ho, meaning that the practicum module has an effect when used in improving student learning outcomes. So it can be concluded that there is an influence when using offline learning assisted by the Serli practicum module on magnetic material on the learning outcomes of sixth grade students of SD Negeri 1 Binangga.Keywords: Offline Learning, Serli Practicum Module, Magnet Material, Learning Outcomes